Cognitive function and depressivity before and after cpap treatment in obstructive sleep apnea patients - Hobzova, Milada; Hubackova, Lia; Vanek, Jakub; Genzor, Samuel; Ociskova, Marie; Grambal, Ales; Prasko, Jan (Neuro endocrinology letters, 2017)
OBJECTIVE: The target of the investigation was to find if there is any improvement of depressive symptoms and cognitive functioning after continuous positive airway pressure (CPAP) treatment in the severe obstructive apnea (OSA) patients. METHOD: The study included 59 patients treated with CPAP for OSA in the Sleep Laboratory of the Department of Respiratory Medicine. Thirty-eight patients were treated with CPAP for one month, and twenty-one patients were in a control group. We used the following methods: Test of Visual Memory (ViMe), Numeric Rectangle, d2 (test of attention), and the Beck Depression Inventory-II, respectively. RESULTS: Among the OSA patients, there were statistically significant improvements in all parameters: attention, working memory, and depressive symptoms after the treatment with CPAP. We found a statistically significant positive connection between the decrease in depressive symptoms and the improvement in attention. In the control group, there were no improvements in the investigated factors. CONCLUSIONS: According to our results, the patients with sleep apnoea improved their mood and cognitive functions during the treatment by the CPAP device.
Keywords: kognice; lidé; Middle Aged; výsledek terapie; Adult; Cognition; neuropsychologické testy; Female; deprese; Attention; Memory; Humans; Neuropsychological Tests; pozornost; paměť; Continuous Positive Airway Pressure; lidé středního věku; mužské pohlaví; Sleep Apnea, Obstructive; obstrukční spánková apnoe; Depression; ženské pohlaví; Treatment Outcome; Male; Aged; trvalý přetlak v dýchacích cestách; dospělí; senioři